Cervical Lymph Node Metastases from Unknown Primary Tumor - Vladimir Milosev (Southeastern European Medical Journal)
Introduction: Metastases of the lymph nodes of the neck originating from cancers of an unknown primary site represent a diagnostic and therapeutic challenge. Metastatic carcinomas of unknown primary site (CUPS) account for about 3-5% of all malignant disease diagnoses. Planocellular carcinomas account for 90% of cancers of unknown site, while the remaining 10% are poorly differentiated and adenocarcinomas.